Challenges and Opportunities of Nanotechnology as Delivery Platform for Tocotrienols in Cancer Therapy - Maniam, Geetha; Mai, Chun-Wai; Zulkefeli, Mohd; Dufès, Christine; Tan, Doryn Meam-Yee; Fu, Ju-Yen (Frontiers in Pharmacology, 2018)
Plant-derived phytonutrients have emerged as health enhancers. Tocotrienols from the vitamin E family gained high attention in recent years due to their multi-targeted biological properties, including lipid-lowering, neuroprotection, anti-inflammatory, antioxidant and anticancer effects. Despite well-defined mechanism of action as an anti-cancer agent, their clinical use is hampered by poor pharmacokinetic profile and low oral bioavailability. Delivery systems based on nanotechnology were proven to be advantageous in elevating the delivery of tocotrienols to tumor sites for enhanced efficacy. To date, preclinical development of nanocarriers for tocotrienols include niosomes, lipid nanoemulsions, nanostructured lipid carriers (NLC) and polymeric nanoparticles. Active targeting was explored via the use of transferrin as targeting ligand in niosomes. In vitro, nanocarriers were shown to enhance the anti-proliferative efficacy and cellular uptake of tocotrienols in cancer cells. In vivo, improved bioavailability of tocotrienols were reported with NLCs while marked tumor regression was observed with transferrin-targeted niosomes. In this review, the advantages and limitations of each nanocarriers were critically analyzed. Furthermore, a number of key challenges were identified including scale-up production, biological barriers and toxicity profiles. To overcome these challenges, three research opportunities were highlighted based on rapid advancements in the field of nanomedicine. This review aims to provide a wholesome perspective for tocotrienol nanoformulations in cancer therapy directed towards effective clinical translation.